Intellectual property rights regimes, their assets, and limitations - Luwedde, Justine; Taylor, Peter; Koo, Jawoo; Chambers, Judith A. (Think7, 2023)
The role of intellectual property has become increasingly important in protecting creations of the mind and making day-to-day business decisions. Hence, if innovations are left unprotected, they can be exploited by competitors with capacity to commercialize them. This policy brief points out that lowand middle-income countries face intellectual property-related challenges compared to high-income countries due to inadequate intellectual property awareness, the high cost of processing patent applications, weak enforcement of intellectual property rights, and weak research and development capacity. Group of Seven (G7) countries are thus better positioned, as high-income countries, to lead globally on intellectual property enforcement, and leverage the flexibilities within the trade related aspects of intellectual property to support and encourage future technologies in low- and middle-income countries. We propose that G7 countries support the creation of equity- and rights-based awareness on intellectual property rights, the improvement of mechanisms and systems for enforcement, and investment in research and development via building local support to reduce costs.